DIGITALISASI SISTEM INFORMASI AKUNTANSI PERSEDIAAN PADA APOTEK PAPUA PALEMBANG - Nazwa Umaya; Yevi Dwitayanti; Sopian AR (Jurusan Akuntansi Politeknik Negeri Sriwijaya Palembang, 2026)
This study aims to design a computer-based inventory accounting information system for Apotek Papua using Microsoft Access as a solution to the shortcomings of manual record-keeping. Data was collected through observation, interviews, and documentation to identify system requirements and evaluate operational procedures. Analysis indicates that the receipt and issuance of goods align with accounting information system principles through verification, recording, and periodic inventory control. A clear organizational structure and the division of tasks between the warehouse and sales departments further support operational efficiency. Supporting documents such as purchase orders, sales invoices, stock cards, and inventory reports serve to facilitate recording and oversight. The designed system provides integrated features ranging from data input and transactions to reporting, thereby improving the accuracy, efficiency, and effectiveness of inventory management. With this system, the company’s internal controls are strengthened because inventory activities can be monitored systematically and transparently, supporting modern and reliable pharmacy operations. Keywords: Accounting Information System, Inventory, Microsoft Access.